EFFECT OF TiO2 AND Ag NANOPARTICLES ON MIGRATION BEHAVIOR OF LEACHATE CONTAMINANTS IN AEROBIC BIOREACTOR LANDFILLS - Guvenc, Senem Yazici; Alan, Burcu; Adar, Elanur; Bilgili, M. Sinan (YILDIZ TECHNICAL UNIV, 2016)
Nowadays, depending on the increase of usage of TiO2 and Ag nanoparticles in consumer products, it is expected that they will reach to sanitary landfills at the end of their useful life. Also, both Ag and TiO2 nanoparticles have a potential to migrate from porous media to groundwater according to the environmental conditions such as pH, ionic strength, concentration of the nanoparticles, and properties of the liner system. Thus, it is an important issue how the impacts of these nanoparticles on migration behaviors of contaminants from landfill leachate to the groundwater. In this study, three pilot-scale aerobic landfill bioreactors were simultaneously operated for a period of 375 days. Three reactors were loaded with solid wastes representing Istanbul municipal solid wastes. In groundwater samples, variations of pH, Cl-, conductivity, alkalinity, chemical oxygen demand, total organic carbon, total nitrogen were investigated. The results of this study showed that migration behavior of leachate contaminants have been very different in the presence of Ag nanoparticles in aerobic bioreactor landfills. It can be concluded that Ag nanoparticles can increase transport of leachate contaminants from landfill leachate to groundwater.
Keywords: Aerobic landfill; leachate; contaminant transport; TiO2 and Ag nanoparticles; MUNICIPAL SOLID-WASTE; ENGINEERED NANOMATERIALS; COMPOSITE LINERS; LIFE-CYCLE; RECIRCULATION; DEGRADATION; NANOSILVER; TRANSPORT; AERATION; PRODUCTS; Engineering